Analisis Ketimpangan Pendapatan di Provinsi Jambi - Wiyan Mailindra (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study is 1) to find out the Gross Regional Domestic Product (PDRB) in jambi province 2) to determinan the development of the population in Jambi Province 3) to find out in income inequality indexin Jambi Province, the anatycal tool used in this study is the development analysis and Wiliamson Index analysis, the result of the development of Gross Regional Domestic Product (GRDP) on average experienced in crease where the biggest increase in 2017 was 174.441.438 or 9,35% and the lowest descrease in 2013 was 130.146.203 or 12,75% then the result of the development of the population number in Jambi Province on average that the index value 0f 0,513 was categorized as moderate, the higgest Wiliamson Index value occurred in 2016 with a value of 0,67 and the lowest Wiliamson Indeks value in years on 2017 with an Indeks value of 0,41 (Medium) from this study is the conclusion of the result of the a study that the development of gross regional domestic product (GRDP) has desrease and the population has increase to analyzed theim balance of the Jambi Province categorized in the category (Medium).